Advances in hydrogel for diagnosis and treatment for Parkinson’s disease - Zhu, Peining; Zhao, Zenghui; Gao, Yufei (Frontiers in Pharmacology, 2025)
Currently, few symptomatic and palliative care options are available for patients with Parkinson’s disease (PD). Interdisciplinary research in materials engineering and regenerative medicine has stimulated the development of innovative therapeutic strategy for patients with PD. Hydrogels, which are versatile and accessible to modify, have garnered considerable interests. Hydrogels are a kind of three-dimensional hydrophilic network structure gels that are widely employed in biological materials. Hydrogels are conspicuous in many therapeutic applications, including neuron regeneration, neuroprotection, and diagnosis. This review focuses on the advantageous applications of hydrogel-based biomaterials in diagnosing and treating the patients with PD, including cell culture, disease modeling, carriers for cells, medications and proteins, as well as diagnostic and monitoring biosensors.